2022
DOI: 10.3390/foods11030399
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Light Sources on the Biochemical Composition of Arthrospira spp. Grown in Model Systems

Abstract: Arthrospira platensis and Arthrospira maxima are prokaryotic microalgae commercially marketed as spirulina. The pigments extracted from these algae are widely used for cosmetic and nutraceutical applications. This work aimed to evaluate the influence of three light-emitting lamps (white, orange and blue) on the growth and biomass composition of two strains of A. platensis (M2 and M2M) and one of A. maxima. The obtained data show strain- and light-dependent responses of the microalgae. In addition, white and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
(53 reference statements)
1
24
2
1
Order By: Relevance
“…For instance, Ravelonandro et al [ 61 ] observed a higher protein content under white compared to green, red, and blue light, respectively. In Milia et al [ 78 ], the protein content of Spirulina was higher under blue and white fluorescent light compared to orange light in the studies by Markou [ 11 ] and da Fontoura Prates et al [ 10 ], and the protein productivity under red or red and green LEDs was higher than under white LEDs. However, the spectral conditions of the light sources were not presented by the authors, which makes it difficult to interpret and compare the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Ravelonandro et al [ 61 ] observed a higher protein content under white compared to green, red, and blue light, respectively. In Milia et al [ 78 ], the protein content of Spirulina was higher under blue and white fluorescent light compared to orange light in the studies by Markou [ 11 ] and da Fontoura Prates et al [ 10 ], and the protein productivity under red or red and green LEDs was higher than under white LEDs. However, the spectral conditions of the light sources were not presented by the authors, which makes it difficult to interpret and compare the results.…”
Section: Resultsmentioning
confidence: 99%
“…Tayebati et al [ 60 ] found the highest phycocyanin content under monochromatic red LED light (with 660 nm peak), which was higher than white, yellow (with 590 nm peak), and blue light conditions. Milia et al [ 78 ], investigated the effect of white, orange, and blue light treatment on the phycocyanin content of A. platensis M, A. platensis M2M, and A. maxima , indicating that various Spirulina strains show different responses in the cellular phycocyanin content towards changing light color conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, earlier reports about the influence of light color on the quantity and quality of AP biomass are inconsistent. Most studies revealed that red light could induce the strongest growth and blue light the least [ 34 , 37 , 50 , 51 , 52 , 53 , 54 ]. In contrast to these results, Chainapong et al reported a higher growth rate of AP under white light in comparison to blue, red and yellow lights, while Ravelonandro found that the final biomass of AP exposed to green or white light was higher compared to red light [ 38 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In complete contrast to our results, in two studies the highest growth rate was found under blue light; Madhyastha observed the greatest growth in A. fusiformis in blue light and the least in red light [ 36 ], and Bahman et al reported that—also for AP—the highest biomasses were observed under blue light [ 56 ]. These varying findings might result from differences in the microalgal strains (slight differences are reported even among AP strains), experimental setup and realization of the studies [ 51 ]. This may comprise differences in the light sources, cultured AP species ( A. platensis , A. maxima and A. fusiformis ), composition of the culture medium, aeration rates, pH value, culture temperature and/or illumination periods and intensities.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, Spirulina is produced industrially under controlled conditions [ 23 ]. In fact, the growth and productivity of this microorganism depend on several factors such as nutrient concentration, temperature, the light spectrum, intensity, and pH, which also influence its biochemical composition [ 40 , 41 ]. Furthermore, Spirulina is used in medicine to treat different health conditions thanks to bioactive compounds such as antioxidants, immuno-stimulants, anti-inflammatory, antibacterial, antiviral, antitumor, antiallergic, antidiabetic, including phenolics, phycobiliproteins, and chlorophyll [ 20 , 21 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%